The book of candlelight - Adams, Ellery (Adams, Ellery. Secret, Book, and Scone Society novel, 2020)
As the owner of Miracle Books, Nora Pennington figures all the wet weather this spring is at least good for business. The local inns are packed with stranded travelers, and among them Nora finds both new customers and a new friend, the sixtysomething Sheldon, who starts helping out at the store. Since a little rain never hurt anyone, Nora rides her bike over to the flea market one sodden day and buys a bowl from Danny, a Cherokee potter. It<U+2019>ll make a great present for Nora<U+2019>s EMT boyfriend, but the next day, a little rain turns into a lot of rain, and the Miracle River overflows it banks. Amid the wreckage of a collapsed footbridge, a body lies within the churning water. Nora and the sheriff both doubt the ruling of accidental drowning, and Nora decides it<U+2019>s time for the Secret, Book, and Scone Society to spring into action. When another body turns up, it becomes clearer that Danny<U+2019>s death can<U+2019>t be blamed on a natural disaster. A crucial clue may lie within the stone walls of the Inn of Mist and Roses: a diary, over a century old and spattered with candle wax, that leads Nora and her friends through a maze of intrigue<U+2014>and onto the trail of a murderer . . .